Business forecasting - Hanke, John E., 1940-; Wichern, Dean W. (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2009)
Written in a simple, straightforward style, Business Forecasting 9/e presents basic statistical techniques using practical business examples to teach students how to predict long-term forecasts.
1. Introduction to Forecasting -- 2. A Review of Basic Statistical Concepts -- 3. Exploring Data Patterns and Choosing a Forecasting Technique -- 4. Moving Averages and Smoothing Methods -- 5. Time Series and Their Components -- 6. Simple Linear Regression -- 7. Multiple Regression Analysis -- 8. Regression with Time Series Data -- 9. The Box-Jenkins (ARIMA) Methodology -- 10. Judgmental Forecasting and Forecast Adjustments -- 11. Managing the Forecasting Process
ncludes bibliographical references and index.
1
Keywords: Business forecasting